Motivating Santri to Choose Islamic Boarding Schools as a Means of Shaping Islamic Character - Ummil Khurriyah; Budi Haryanto (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine, understand, and describe the motivation of students to choose Islamic boarding schools as a means of forming Islamic character and the most dominant motivational factors for students in Sungon Hamlet. This type of research is qualitative using a naturalistic approach. Sources of data obtained are primary and secondary data sources. Data collection techniques were carried out by means of observation, interviews and documentation. While the technique of data analysis and interpretation by means of data reduction, data presentation and data verification. The results of this study reveal that students choose Islamic boarding schools as a means of forming Islamic character because they get encouragement from their parents. In addition, there is self-motivation. Because every parent wants a child who has noble character, is good at the Koran, avoids negative actions and is able to know the teachings of Islam widely. Factors that motivate students to choose Islamic boarding schools as a means of character building are dominated by external factors. The factors that encourage students to choose Islamic boarding schools are factors from their parents and factors that grow from within themselves. So, it can be concluded that the factor that encourages students to continue their education in Islamic boarding schools and aims to build their character is that the majority of the encouragement comes from their parents.